BMJ quality improvement reports.
"BMJ Quality Improvement Reports aims to publish a high volume of quality improvement reports to help healthcare professionals document and share innovations and excellence in care. It is an online-only, open access general healthcare journal. Publishing procedures are built around a light-touch peer review process and continuous publication. Reports are published online as soon as the article is ready. BMJ Quality Improvement Reports is not an edition or supplement of the BMJ."